Artifacts in Musculoskeletal Ultrasonography - Taljanovic, Mihra S.; Melville, David M.; Scalcione, Luke R.; Gimber, Lana H.; Lorenz, Eileen J.; Witte, Russell S. (Seminars in Musculoskeletal Radiology, 2014)
During the past 2 decades, high-resolution ultrasonography (US) has been increasingly utilized in the diagnosis of musculoskeletal trauma and diseases with results comparable with MR imaging. US has an advantage over other cross-sectional modalities in many circumstances due to its superior spatial resolution and ability to allow dynamic assessment. When performing musculoskeletal US, the examiner has to be knowledgeable in the complex anatomy of the musculoskeletal system and US imaging technique. Additionally, he or she must be familiar with several common imaging artifacts in musculoskeletal US that may be mistaken for pathology, as well as several artifacts that frequently accompany pathologic conditions. These artifacts may occur with both B-mode gray-scale and Doppler imaging. In this article, we discuss common artifacts seen in musculoskeletal US and techniques to avoid or minimize these artifacts during clinical US examinations.
Keywords: ultrasonography; ultrasound; artifact; anisotropy; posterior acoustic shadowing; posterior acoustic enhancement; increased through transmission; posterior reverberation; ring-down artifact; comet-tail artifact; mirror image; beam width artifact; side-lobe artifact; background noise; aliasing; twinkling artifact